2007
DOI: 10.1111/j.1365-2818.2007.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐selective colloidal‐gold localization in transmission X‐ray microscopy

Abstract: Key words. colloidal gold, image analysis, soft X-ray microscopy. SummaryColloidal gold is a useful marker for functional-imaging experiments in transmission X-ray microscopy. Due to the low contrast of gold particles with small diameters it is necessary to develop a powerful algorithm to localize the single gold particles. The presented image-analysis algorithm for identifying colloidal gold particles is based on the combination of a threshold with respect to the local absorption and shape discrimination, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finally, we note that the microscope can be used for high‐resolution imaging with chemical contrast in addition to the natural contrast, employing colloidal gold markers. Stollberg et al (2007), recently demonstrated an image‐analysis algorithm for the size‐selective localization of single colloidal‐gold particles in cell like structures. Gold particles down to a size of 50 nm could clearly be identified and localized by this algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that the microscope can be used for high‐resolution imaging with chemical contrast in addition to the natural contrast, employing colloidal gold markers. Stollberg et al (2007), recently demonstrated an image‐analysis algorithm for the size‐selective localization of single colloidal‐gold particles in cell like structures. Gold particles down to a size of 50 nm could clearly be identified and localized by this algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…6). Gold immunolabeling and quantum dots (Stollberg et al, 2007) can also help to image structures bound to specific functional groups.…”
Section: Examples Of Full‐field X‐ray Imaging Of Biomaterialsmentioning
confidence: 99%
“…No staining is required for imaging with either TXM or microprobe, thus, the biochemistry of the original samples can be preserved. However, immunolabeling, e.g., with gold nanoparticles can be used to identify regions of biological tissue with specific proteins or functional groups (Stollberg et al, 2007) for further insight into physiology.…”
Section: Examples Of Full‐field X‐ray Imaging Of Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques have been successfully employed to enhance contrast in images obtained with an SXR microscope [9]. Image analysis can also be used to map the location of markers such as gold nanoparticles, commonly used in biological imaging applications [10], or to determine the position of latex nanospheres in three dimensions [11]. In general, these tools are based on a wavelet analysis.…”
Section: Introductionmentioning
confidence: 99%